Evaluation of CT findings among Headache Patients at Neurology OPD in a Tertiary Care Hospital: A retrospective study - Wadud, Shaheen; Khan, Nurul Amin; Islam, Torikul; Biswas, Eshita; Sakib, MAM; Khan, SM Dastegir (Journal of Dhaka National Medical College & Hospital, 2021)
Background: Headache is the most common complain of the patients presenting to Radiology Department for the purpose of doing a CT scan for headache evaluation. Objective: (1) To find out the organic cause in patients with chronic headache with or without neurologic abnormality with the use of computed tomography (CT), (2) to know the age prevalence, (3) to know the sex variation. Methods: All patients with complaints of chronic headache in the Department of Neurology OPD from August 2018 to July 2019 were included in the study. Total of 220 cases were included. Patients were divided into three groups based on CT scan findings: (1)Those with normal CT scan, (2) Those with minor abnormality (Not altering the patient management), (3) Those with clinically significant abnormality (Altering the management protocol). Results were tabulated and analyzed for the diagnostic yield from imaging in evaluation of patient with history of headache. Results: Out of 220 patients, 128 had normal CT (58.18%) and 92 (41.82%) had abnormal CT findings. Among the abnormal CT findings major and minor abnormalities constitute 17.27% and 24.55% respectively that will help in further management. Headache is common in both male (52.73%) and female (47.27%). No significant difference between them. Most common age group affected is 41-60 years (35%) Conclusion: The prevalence of intracranial abnormalities detected by CT scan in this study was almost similar to previous studies provided normal neurological examinations. In the absence of neurological abnormality, CT scan did not offer minimum advantages. J. Dhaka National Med. Coll. Hos. 2021; 27 (02): 19-21